Bibliometric Study of Managing Generational Diversity in the Workplace - Judijanto, Loso; Winanto , Ahmad; Setiyawan, Agus (Westscience Press, 2024)
Managing generational diversity in the workplace has become a critical focus for organizations as they navigate the challenges and opportunities presented by multigenerational teams. This study employs a bibliometric analysis to explore the trends, key themes, and global collaboration patterns in generational diversity research from 2000 to 2024. Using data from Scopus, the study identifies influential topics such as diversity, inclusion, leadership, and communication, which are central to managing generational dynamics. Leadership was found to be a pivotal factor in bridging generational divides, while communication gaps and generational stereotypes remain persistent challenges. The analysis also highlights the dual role of technology as both a barrier and a tool for fostering intergenerational collaboration. Despite significant contributions from developed countries, there is notable underrepresentation from developing regions, emphasizing the need for more inclusive research efforts. Emerging topics, including mental health and intersectionality, suggest avenues for future exploration. This study contributes valuable insights for researchers, practitioners, and policymakers aiming to create inclusive, adaptive, and effective multigenerational workplaces.